2018
DOI: 10.33687/pbg.006.01.2449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Diversity in Barley (Hordeum vulgare) Genotypes using Protein Profiling

Abstract: The knowledge of the genetic diversity of barley (Hordeum vulgare) genotypes based on protein polymorphism is very important for breeding programs. The purpose of the current study was to determine the genetic diversity and relationships among ten barley genotypes by using Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) for protein profiles. A total number of 30 bands with molecular weights ranging from 12 to 148 KD were detected. Out of these, five bands were observed monomorphic. Rest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
(25 reference statements)
3
3
0
Order By: Relevance
“…The cause to find the levels of diversity in some cultivars could be that their proteins are controlled by quantitative gene families that have arisen by divergence from an ancestral gene through chromosomes aberration. These finding agree with pervious research (Tahir 2014;Mzid et al, 2016 andEid 2018).…”
Section: Cluster Analysis Based On Combined Proteins and Rapds Datasupporting
confidence: 94%
See 2 more Smart Citations
“…The cause to find the levels of diversity in some cultivars could be that their proteins are controlled by quantitative gene families that have arisen by divergence from an ancestral gene through chromosomes aberration. These finding agree with pervious research (Tahir 2014;Mzid et al, 2016 andEid 2018).…”
Section: Cluster Analysis Based On Combined Proteins and Rapds Datasupporting
confidence: 94%
“…On the other hand, Giza 123 cultivar formed a separate cluster indicating the genetic background of the Giza 123 cultivar was distinct from all cultivars. The results almost agree with Manal Eid (2018) who studied the genetic polymorphism using SDS-proteins patterns. Her results produced 30 bands with MW ranging from 12 to 148 KD, of which only 5 bands varied among the accessions with polymorphism (83.3%).Her results also separated Giza123 cultivar from the other cultivars.…”
Section: Cluster Analysis Based On Combined Proteins and Rapds Datasupporting
confidence: 88%
See 1 more Smart Citation
“…Protein profile analysis of cowpea accessions using SDS-PAGE revealed 17 bands with a range of molecular weights from 8.30-251.39 kDa and six polymorphic bands detected. These results are corroborated by the findings of two findings 31,32 . The polymorphic bands were observed in TVu596, TVu10710, TVu4467, TVu5590, TVu8063 and TVu11883 with low molecular weights ranging from 15.44-14.85 kDa.…”
Section: Discussionsupporting
confidence: 83%
“…It had been reported that cowpea is among the 5th top food legumes that are grown worldwide and has a presence on every continent except Oceania and Australia 31 . The west African sub-region contributes about 95% of global cowpea production, with Nigeria being the largest producer in the world 32 . This notwithstanding, cowpea landraces are dramatically disappearing and unfortunately being replaced by improved, higher yielding modern cultivars from modern breeding programmes 35,36 and this has resulted to erosion of crop genetic diversity 31 .…”
Section: Discussionmentioning
confidence: 99%